Accounts of preventative coping: an interview study of stroke survivors on general practice registers. Issue 9 (5th September 2022) - Scott Reid, Peter; Neville, Emma; Cater, Frances; Mullis, Ricky; Mant, Jonathan; Duschinsky, Robbie
Abstract : Objectives: Preventative coping is an underexplored aspect of coping behaviour. Specifically, coping is a key concern in stroke survivor accounts, but this has yet to be investigated with reference to secondary prevention. Design: Secondary analysis of a qualitative data set comprising semistructured interviews of 22 stroke survivors recruited from five general practices in the East of England. The topic guide included exploration of advice and support given by their doctor on medication and lifestyle. The interviews were coded using thematic analysis. Results: The accounts emphasised individual responsibility. Two key themes were identified, which foregrounded the role of self-concept for coping: (a) striving to be 'good', (b) appeal to ideas of 'personality'. In the former, preventative behaviour was depicted in moralistic terms, with the doctor as an adjudicator. In the latter, participants attributed their coping behaviour to their personality, which might help or hinder these efforts. Conclusions: We highlight that coping was characterised by survivors as something enacted by the individual self, and consider how constructions of self may impact preventative coping efforts.